Performance of a vascular anomaly center: a retrospective analysis of 461 cases over seven years - Strübing, Felix; Laurich, Annette; Weiß, Christel; Schönberg, Stefan; Kneser, Ulrich; Sadick, Maliha (Acta radiologica, 2023)
Background - Vascular malformations are rare diseases that are best managed in multidisciplinary vascular anomaly centers (VAC). So far, there are few published data on the logistic structure, patient allotment, and internal workflow in an interdisciplinary VAC. - Purpose - To demonstrate the referral structure and patient allotment in a European VAC. - Material and Methods - A retrospective cohort study was conducted. All patients treated in the VAC since its establishment in April 2014 until June 2020 were identified. A total of 461 patients were included in this study. - Results - Most often, a venous malformation was diagnosed (49.9%), followed by arteriovenous malformations (8.7%) and syndromal vascular malformations (8.2%). Only 45.1% of referral diagnoses were correct. Of referrals, 35.1% were internal on-campus references, 28.0% were external references through physicians in private practice, and 19.7% came via external cooperating hospitals. Of the patients, 17.1% were self-admissions without a referral. - Conclusion - The most important referring clinics are internal medicine, pediatric, and vascular surgery. A substantial proportion of referrals came from private practices. Recruiting these cooperation partners should be considered a high priority when establishing a new VAC. The rate of misdiagnosis is high, and more education of fellow clinicians is urgently needed. Therefore, patients with vascular malformations should be referred to and treated in dedicated centers for vascular anomalies.
Erstmals online veröffentlicht: 13. Oktober 2022
Gesehen am 29.07.2024